The Impact of Cefuroxime Susceptibility on Aeromonas Necrotizing Fasciitis Outcomes - Tsung-Yu Huang; Shu-Fang Kuo; Yao-Hung Tsai; Jiun-Liang Chen; Kuo-Ti Peng; Yao-Kuang Huang; Chien-Hui Hung; Yen-Yao Li; Hsing-Jung Li; Cheng-Ting Hsiao; Wei-Hsiu Hsu (Microorganisms, 2023)
Despite aggressive antibiotic therapy and surgical debridement, Aeromonas necrotizing fasciitis (NF) can lead to high amputation and mortality rates. Our study compares the different antibiotic minimum inhibitory concentrations (MICs) via Epsilometer tests (E-tests) between non-survivors and survivors of Aeromonas NF of limbs. A prospective review of 16 patients with Aeromonas NF was conducted for 3.5 years in a tertiary coastal hospital. E-tests were conducted for 15 antimicrobial agents to determine the MIC value for Aeromonas species. These patients were divided into non-survival and survival groups. The clinical outcomes, demographics, comorbidities, presenting signs and symptoms, laboratory findings, and microbiological results between the two periods were compared. A total of four patients died, whereas 12 survived, resulting in a 25% mortality rate. A higher proportion of bloodstream infections (100% vs. 41.7%; p = 0.042), monomicrobial infections (100% vs. 33.3%; p = 0.021), shock (100% vs. 33.3%; p = 0.021), serous bullae (50% vs. 0%; p = 0.009), liver cirrhosis (100% vs. 25%; p = 0.009), chronic kidney disease (100% vs. 33.3%; p = 0.021), lower susceptibility to cefuroxime (25% vs. 83.3%; p = 0.028), and ineffective antibiotic prescriptions (75% vs. 16.7%; p = 0.029) was observed in non-survivors. Aeromonas NF is an extremely rare skin and soft-tissue infection that is associated with high mortality, bacteremia, antibiotic resistance, and polymicrobial infection. Therefore, antibiotic regimen selection is rendered very challenging. To improve clinical outcomes and irrational antimicrobial usage, experienced microbiologists can help physicians identify specific pathogens and test MIC.